Recent Trends in Admission Diagnosis and Related Mortality in the Medically Critically Ill. (February 2022) - Ingraham, Nicholas E.; Vakayil, Victor; Pendleton, Kathryn M.; Robbins, Alexandria J.; Freese, Rebecca L.; Palzer, Elise F.; Charles, Anthony; Dudley, R. Adams; Tignanelli, Christopher J.
Purpose: With decades of declining ICU mortality, we hypothesized that the outcomes and distribution of diseases cared for in the ICU have changed and we aimed to further characterize them. Study Design and Methods: A retrospective cohort analysis of 287, 154 nonsurgical-critically ill adults, from 237 U.S. ICUs, using the manually abstracted Cerner APACHE Outcomes database from 2008 to 2016 was performed. Surgical patients, rare admission diagnoses (<100 occurrences), and low volume hospitals (<100 total admissions) were excluded. Diagnoses were distributed into mutually exclusive organ system/disease-based categories based on admission diagnosis. Multi-level mixed-effects negative binomial regression was used to assess temporal trends in admission, in-hospital mortality, and length of stay (LOS). Results: The number of ICU admissions remained unchanged (IRR 0.99, 0.98-1.003) while certain organ system/disease groups increased (toxicology [25%], hematologic/oncologic [55%] while others decreased (gastrointestinal [31%], pulmonary [24%]). Overall risk-adjusted in-hospital mortality was unchanged (IRR 0.98, 0.96-1.0004). Risk-adjusted ICU LOS (Estimate −0.06 days/year, −0.07 to −0.04) decreased. Risk-adjusted mortality varied significantly by disease. Conclusion: Risk-adjusted ICU mortality rate did not change over the study period, but there was evidence of shifting disease burden across the critical care population. Our data provides useful information regarding future ICU personnel and resource needs.